2020
DOI: 10.1002/chir.23283
|View full text |Cite
|
Sign up to set email alerts
|

Homochiral bifunctional L‐prolinamide‐ and L‐bis‐prolinamide‐catalyzed asymmetric aldol reactions performed in wet solvent‐free conditions

Abstract: In this study, the novel bifunctional homochiral thiourea-L-prolinamides 1-4, tertiary amino-L-prolinamide 5, and bis-L-prolinamides 6 and 7 were prepared from enantiomerically pure (11R,12R)-11,12-diamino-9,10-dihydro-9,10-ethanoanthracene 8 and (11S,12S)-11,12-diamino-9,10-dihydro-9,10-ethanoanthracene ent-8. Highly enantioselective and diastereoselective aldolic intermolecular reactions (up to 95% enantiomeric excess, 93:7 anti/syn) between aliphatic ketones (20 equiv) and a range of aromatic aldehydes (1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…This property raises the pKa value, placing proline ahead of other amino acids in terms of nucleophilicity [6]. The earliest discovery reported that proline is a "microaldolase", which is capable of activating the electrophile by its proton donor group, and also activating the nucleophile by its amine group [7]. This permits proline to take part in bifunctional asymmetric catalysis, which has been a successful laboratory strategy for enhancing chemical transformations [8].…”
Section: Introduction 11 Prolinementioning
confidence: 99%
“…This property raises the pKa value, placing proline ahead of other amino acids in terms of nucleophilicity [6]. The earliest discovery reported that proline is a "microaldolase", which is capable of activating the electrophile by its proton donor group, and also activating the nucleophile by its amine group [7]. This permits proline to take part in bifunctional asymmetric catalysis, which has been a successful laboratory strategy for enhancing chemical transformations [8].…”
Section: Introduction 11 Prolinementioning
confidence: 99%